A FEW REMARKS ON THE LEGAL STATUS OF DAOS IN THE EUROPEAN UNION AND THE REPUBLIC OF ARMENIA - Zięty, Jakub Jan; Pietraszuk, Rafał (State and Law, 2026)
The development of blockchain technology has led to the emergence of a novel form of collaborative organization, known as Decentralized Autonomous Organizations (DAOs), which rely on internet-based communication and cryptographic mechanisms. The economic significance of DAOs has prompted legislators to consider appropriate legal frameworks. This article analyzes the legal status of DAOs in the European Union and the Republic of Armenia. While the EU adopted the Markets in Crypto-Assets Regulation (MiCA), it refrained from recognizing DAOs as distinct legal entities, despite preliminary considerations during the legislative process. Similarly, Armenia, through the Law on Crypto-Assets (HO-159-N), inspired by MiCA, does not explicitly address DAOs. Consequently, both jurisdictions exhibit a regulatory gap. The article demonstrates that, even in the absence of dedicated legislation, interpretative cues within these legal instruments can provide guidance on how DAOs may be treated under EU and Armenian law. By examining these frameworks, the study contributes to understanding the potential legal recognition and regulation of DAOs in different legal systems.
Keywords: Decentralized Autonomous Organizations; crypto-assets regulation; legal status; European Union; Armenia; blockchain technology